Application of m6A and TME in Predicting the Prognosis and Treatment of Clear Cell Renal Cell Carcinoma. (4th March 2022) - Pei, Dongchen; Xu, Chaojie; Wang, Dong; Shi, Xiaoxue; Zhang, Yurui; Liu, Yi; Liu, Nan; Guo, Jianhua; Yu, Yang; Kang, Zhengjun; Zhu, Haipeng
Abstract : Background . Previous studies have shown that RNA N6-methyladenosine (m 6 A) plays an important role in the construction of the tumor microenvironment (TME). However, how m 6 A plays a role in the TME of clear cell renal cell carcinoma remains unclear. Methods . Based on 23 m 6 A modulators, we applied consensus cluster analysis to explore the different m 6 A modification profiles of ccRCC. The CIBERSORT method was employed to reveal the correlation between TME immune cell infiltration and different m 6 A modification patterns. A m 6 A score was constructed using a principal component analysis algorithm to assess and quantify the m 6 A modification patterns of individual tumors. Results . Three distinct m 6 A modification patterns of ccRCC were identified. The characteristics of TME cell infiltration in these three patterns were consistent with immune rejection phenotype, immune inflammation phenotype, and immune desert phenotype. In particular, when m 6 A scores were high, TME was characterized by immune cell infiltration and patient survival was higher (p < 0.05 ). When m 6 A scores were low, TME was characterized by immunosuppression and patient survival was lower (p < 0.05 ). The immunotherapy cohort confirmed that patients with higher m 6 A scores had significant therapeutic advantages and clinical benefits. Conclusions . The m 6 A modification plays an important role in the formation of TME. The m 6 A scoring system allows the identification of m 6 A modification patterns in individual tumors, discriminates the immune infiltrative features of TME, and provides more effective prognostic indicators and treatment strategies for immunotherapy.